Examining Host Selection by Mexican Bean Beetle (Coleoptera: Coccinellidae) Using Mark-Release-Recapture. Issue 1 (17th February 2019) - Nottingham, Louis B; Kuhar, Thomas P
Abstract: Mexican bean beetle, Epilachna varivestis Mulsant, is a pest of snap bean and lima bean in the eastern United States. This pest is susceptible to many insecticides available to conventional growers; however, organic management using parasitoid releases and organic insecticides have inconsistent results. In the interest of developing cultural management techniques such as trap crops or push–pull systems, five bean cultivars were evaluated for preferential host selection by E. varivestis using marked beetles in field cages and open plots. Beetles were marked with a water-based paint pen and their locations on plants monitored over time. In field cages, the purple wax bean, Dragon's Tongue (DT), was preferred over yellow wax, green bean and lima bean; soybean was the least preferred overall. Recaptures of E. varivestis adults in open field plots progressively decreased following beetle release, suggesting the affinity of adults to disperse despite being on or near acceptable hosts. The two wax beans were equally preferred in open field experiments, partially more than the green and lima bean and consistently more than the soybean. These experiments suggest that DT may be a suitable crop for trap cropping or attract and kill strategies for E. varivestis .